A presumed case of Darbepoetin‐induced myocardial infarction in the patient with MDS‐RARS. Issue 4 (18th February 2020) - Zafar, Aneeqa Ahsan; Kouides, Peter
Abstract: Our case is only the 2nd such reported case of atherothrombosis from ESAs and highlights the increased risk of cardiovascular events in patients receiving erythropoietin‐stimulating agents specially patients with underlying MDS where targeting a lower hemoglobin goal and optimizing other cardiovascular risk factors might be beneficial in preventing future cardiovascular mortality. Abstract : Our case is only the 2nd such reported case of atherothrombosis from ESAs and highlights the increased risk of cardiovascular events in patients receiving erythropoietin‐stimulating agents specially patients with underlying MDS where targeting a lower hemoglobin goal and optimizing other cardiovascular risk factors might be beneficial in preventing future cardiovascular mortality.